Digital Marketing: Near Future and Perspectives (European Journal of Economics, Finance and Business Development, 2023)
Digital marketing remains a dynamic and important segment of the marketing landscape. Several trends and prospects are expected shortly. The role of social media will continue to grow, providing companies with opportunities to effectively interact with the audience. Video content will become an even more popular and in-demand format for marketing campaigns. Artificial intelligence and automation will be used to improve efficiency and personalize marketing efforts. Virtual and augmented reality technologies will find their application in creating unique and attractive customer experiences. Analytics and marketing tools will become more advanced, allowing you to more accurately measure results and optimize campaigns. In addition, paying more attention to ethical issues in the collection and use of data will become an integral part of digital marketing. All of these trends indicate that digital marketing will continue to evolve and remain a key tool for companies looking to succeed in the online world.